Peningkatan Hasil Belajar Bahasa Indonesia Menggunakan Metode Inkuiri dengan Media Konkret pada Peserta Didik Palangkaraya: Improving the Results of Learning Indonesian Using the Inquiry Method with Concrete Media in Palangkaraya Students - Helpy Patriana Arifien; Suniati Suniati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to describe the learning activities of students in learning Indonesian Language using inquiry methods with concrete media on class II-A students at Panarung Palangkaraya 5 Elementary School in the 2016/2017 academic year, and improve learning outcomes in Indonesian using inquiry methods with real press on the second grade students of SDN 5 Panarung Palangkaraya 2016/2017 academic year. This type of research is Class Action Research. The research subjects were class II-A students at SDN 5 Palangkaraya, totalling 29 students consisting of 19 male students and ten female students. Data collection techniques in this study used tests and observations. Data analysis uses qualitative and quantitative data analysis. The results showed that Indonesian language learning activities of class II-A students at Panarung SDN-5 Palangkaraya. The average score obtained by students in the first cycle is 3.56 and the average rating in the second cycle is 3.57 with perfect criteria. There is an increase in Indonesian language learning outcomes of class II-A students at Panarung Palangkaraya SDN-5 with the application of inquiry methods with real media. The initial test of the average value of students obtained was 69.96, and classical completeness was 44.82%. The average cost after the application of the inquiry method with real media increased in the first cycle of 79.96, and artistic integrity was 82.75%, and more increased in the second cycle with an average value of 87.86 and 100% classical completeness.